Radiation exposure to comforters and carers during paediatric molecular radiotherapy. Issue 2 (4th October 2014) - Gains, J. E.; Walker, C.; Sullivan, T. M.; Waddington, W. A.; Fersht, N. L.; Sullivan, K. P.; Armstrong, E.; D'Souza, D. P.; Aldridge, M. D.; Bomanji, J. B.; Gaze, M. N.
<x xml:space="preserve">Abstract</x> Background To show whether the incidental radiation exposure received by comforters and carers of children undergoing molecular radiotherapy was kept as low as reasonably achievable and was within English national dose constraints. Procedure The radiation exposure of adult comforters and carers was routinely monitored with a whole body personal dose meter while the child was in hospital. Data were collected on iodine‐131 meta‐iodobenzylguanidine (131I‐mIBG), lutetium‐177 DOTATATE (177Lu‐DOTATATE), and iodine‐131 sodium iodide (131I‐NaI) treatments. Results Data were available for 50 treatments with high‐administered activity double‐infusion 131I‐mIBG and 12 single administrations; 15 177Lu‐DOTATATE treatments and 28 131I‐NaI administrations. The median age was 7 years (1–18). The median administered activity of: 131I‐mIBG was 16.2 GBq (6.8–59 GBq) for double infusion patients and 8.1 GBq (5.26–16.25 GBq) for single administrations; 177Lu‐DOTATATE was 7.2 GBq (2.5–7.5 GBq); and 131I‐NaI was 3 GBq for thyroid remnant ablation and 5.5 GBq for cancer therapy. The median number of comforters and carers for all administrations was 2 (range 1–9). The median exposure values for comforters and carers for high‐administered activity 131I‐mIBG administrations was 302 µSv (0–5282 µSv); for single fraction 131I‐mIBG 163 µSv (3–3104 µSv); 177Lu‐DOTATATE 6 µSv (1–79 µSv); and 131I‐NaI 37 µSv (0–274 µSv). Only one of the comforters and carers exceeded the dose constraint of 5 mSv. Conclusions Doses to comforters and carers were in all but one case within the dose constraint nationally recommended by the Health Protection Agency, now part of Public Health England. New evidence is presented which show that comforter and carer radiation exposure levels from paediatric molecular radiotherapy in routine clinical practice are acceptably low. Pediatr Blood Cancer 2015;62:235–239. © 2014 Wiley Periodicals, Inc.